2021
DOI: 10.31219/osf.io/vxg9r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A model of factors affecting domestic tourist satisfaction on eco-tourism service quality in the Mekong Delta, Vietnam

Abstract: The objective of the present study is to explore the factors affecting domestic tourists’ satisfaction with the quality ofecotourism services. Survey data collected from 457 visitors visiting Mekong Delta, Vietnam were analyzed to provide evidence.Results from multiple regression analysis using SPSS software have determined that Food and beverage Shopping & entertainment services, Perceived price, Nature destination landscape, Security and Safety, Transportation had positive associations with domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous research has shown that various factors of river tourism affect visitor satisfaction. These factors include the quality of infrastructure, safety and security, accessibility, and environmental factors (Giao et al, 2021). Insufficient marketing strategies on river tourism can also prevent the industry from reaching its full potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that various factors of river tourism affect visitor satisfaction. These factors include the quality of infrastructure, safety and security, accessibility, and environmental factors (Giao et al, 2021). Insufficient marketing strategies on river tourism can also prevent the industry from reaching its full potential.…”
Section: Literature Reviewmentioning
confidence: 99%